أثر استخدام الحاسوب التعليمي عي تحصيل تلاميذ الثالثة ثانوي علمي في مادة العلوم الطبيعية - بخوش، وليد عبدالعزيز; حمداوي، عمر (جامعة قاصدي مرباح - مخبر تطوير الممارسات النفسية والتربوية, 2012)
هدفت هذه الدراسة إلى معرفة أثر استخدام الحاسوب في التحصيل الدراسي لتلاميذ السنة الثالثـة ثـانوي علمي في مادة العلوم الطبيعية في المستويات المعرفية الدنيا (الحفظ ، التذكر) والمتوسطة (التحليل، التركيب التصنيف ) والعليا ( التوليد، التكامل) ولتحقيـق هـذا الهدف تم اعتماد المنهج التجريبي لتصـميم التجربـة القائمة على مجموعتين، تتكون كل منهما من ثمانيـة وعشرين تلميذا، تم تـدريس الأولـى مـادة العلـوم الطبيعية باستخدام الحاسوب والثانية درست بالطريقة التقليدية. خضعت المجموعتان لاختبار قبلـي وآخـر بعدي وقد دلت نتائج تحليل الاختبار القبلي على عـدم وجود فروق ذات دلالة إحصائية مما يدل على تكـافؤ المجموعتين، أما نتائج تحليل الاختبار البعدي فقد دلت على ما يلي:\ 1-\ توجد فروق ذات دلالة إحصائية في تحصيل مادة العلوم الطبيعية بين المجموعتين لصـالح المجموعـة التجريبية.\ 1-1-\ لا توجد فـروق ذات دلالـة إحصـائية فـي المستوى المعرفي الأدنى ( الحفـظ، التـذكر) بـين المجموعتين التجريبية \ 1-2-\ توجد فروق والضابطة. ذات دلالة إحصائية في المستوى المعرفي المتوسط (التحليل، التركيب ، التطبيق ) بين المجموعة التجريبية والضابطة لصـالح المجموعـة التجريبية.\ 1-3-\ توجد فروق ذات دلالة إحصائية في المستوى المعرفي الأعلى ( التوليد، التكامل) بـين المجموعـة التجريبية والضابطة لصالح المجموعة التجريبية. The purpose of this study is to discover the effects of computer use in the \ scientific acquisition in school by students of the third secondary year in \ \ the Natural Sciences Subject; at the basic knowledge level (learning, memorizing), as well as the medium (analyzing, synthesis, classification) and the highest level (creation and complementarily). To achieve this aim, an experimental method was followed to test an experiment, in which two groups of 28 student were tested. One of each group \ was taught natural sciences by computer, \ and the second was taught by the traditional method. The two groups were submitted to two tests: one preceding and the other following the experience. Results of the \ pre-experience \ test indicated that there were no significant statistical differences between students, and it found equality between the two groups. However, the post-experience results came as follows: \ \ 1- There were significant statistical differences in the acquisition of the natural sciences subject between the two groups, in favour of the experimental \ .\ group \ 1-1-There were no significant statistical differences at the basic knowledge level (learning, memorizing) between the two groups; 1-2- There were significant statistical differences \ between the \ experimental group and controlled group at the medium level. \ \ 1-3- There were significant statistical differences between the experimental \ and controlled groups at the highest level, in favour of the first one.
Keywords: التحصيل الدراسي -- الجزائر -- طلاب المدارس الثانوية -- التدريس بالحاسوب -- تدريس العلوم الطبيعية -- الوسائل التعليمية -- الأهداف التربوية -- التقييم التربوي